Komunikasi Interpersonal Dalam Menciptakan Keluarga Sakinah - Oci Asti Herni; Sapta Sari; Yanto Yanto (Universitas Dehasen Bengkulu, 2024)
This study aims to identify and analyze Interpersonal Communication in Creating Sakinah Families. Study of Couples in Early Marriage in Teramang Jaya District, Muko Muko Regency. empathy), support (supportiveness), positiveness (positiveness), equality (equality), the results of this study show Interpersonal Communication in Creating Sakinah Families Study of Early Marriage Couples in Teramang Jaya District, Muko Muko Regency. This can be seen from the way they convey family problems openly. A sense of empathy, husband and wife couples have high empathy for husband and wife seen from the way they understand problems in the family as well as some couples in Early Age Marriage in Teramang Jaya Subdistrict provide support to husband and wife for the problems they are experiencing. Support, husband and wife give each other support in communicating, seen from the couple as communicants receive information and provide suggestions that are supportive of information from the wife. Positive feelings, positive feelings in interpersonal communication for early age couples are still not well established. However, this couple tries to convey information clearly and accommodates suggestions and criticisms from partners positively. Equality, husband and wife as communicators respect all opinions of both regardless of the problems faced, so that there is equality in communicating without prioritizing personal ego.